Circulating growth hormone releasing factor concentrations in normal subjects and patients with acromegaly. Issue 6443 (25th August 1984) - Penny, E S; Penman, E; Price, J; Rees, L H; Sopwith, A M; Wass, J A; Lytras, N; Besser, G M
Abstract : A highly specific and sensitive radioimmunoassay was developed for measuring circulating growth hormone releasing factor (GRF) in human plasma. Before measuring immunoreactive GRF plasma samples were extracted on to Vycor glass. Immunoreactive GRF concentrations in plasma samples from 37 fasting normal subjects ranged from less than 10 to 60 ng/l (mean 21 ng/l). Fasting concentrations in 76 out of 80 acromegalic subjects were within the normal range, but the remaining four patients had values of 92 to 25 000 ng/l. Of these, only the patient with the highest concentration had evidence of ectopic GRF secretion from a disseminated carcinoid tumour. Two of the others had longstanding pituitary tumours, and the fourth patient had a pituitary growth hormone (GH) secreting tumour proved by its removal and subsequent remission of acromegaly. There was no correlation between serum GH and plasma immunoreactive GRF concentrations, irrespective of whether the patients were untreated or had been given radiotherapy or dopamine agonists. The assay should help elucidate the physiological role(s) of GRF and may also prove useful in differentiating between pituitary and hypothalamic defects in patients with acromegaly.